Ionic Liquid Co-Catalyst Assisted Biodiesel Production From Waste Cooking Oil Using Heterogeneous Nanocatalyst: Optimization and Characterization - Baskar, Gurunathan; Anita, Nalathamalar T.; Jeehoon, Han; Naveenkumar, Rajendran (Frontiers in Nanotechnology, 2022)
In the present work, the biodiesel was produced from waste cooking oil (WCO) using heterogeneous zinc doped iron nanocatalyst and tetrabutylammonium iodide (TBAI) as co-catalyst. The heterogeneous zinc doped iron nanocatalyst was synthesized and characterized. The functional group in the heterogeneous nanocatalyst was confirmed using FTIR analysis, the crystalline nature was studied by XRD analysis, and the size and structure of the nanocatalyst were analyzed by SEM. The optimization of transesterification parameters like oil to methanol molar ratio, zinc doped iron concentration, TBAI concentration, temperature, and time were carried out for the maximum conversion of biodiesel from WCO. At 50 min the maximum biodiesel conversion of 90% was achieved at 55°C with 12% catalyst, 30% co-catalyst, and 1:11 WCO to methanol ratio. The presence of functional groups and the methyl ester composition of the biodiesel from WCO were confirmed by FTIR and GC-MS analysis. The use of zinc doped iron nanocatalyst with TBAI showed good catalytic activity to produce biodiesel from WCO.